2014
DOI: 10.14221/ajte.2014v39n9.10
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Practice: A Spotlight on the Use of Feedback and Conferencing in the First Year of Schooling

Abstract: With the prevalence of statements that refer to a need to "bridge", "narrow" or "close" gaps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It cannot be assumed that students will enter their first year of schooling without any knowledge of letter-sound associations (Nicholas & Paatsch, 2014). Further to this, the collection of entry data and project implementation occurred during the second school term, three months into the school year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be assumed that students will enter their first year of schooling without any knowledge of letter-sound associations (Nicholas & Paatsch, 2014). Further to this, the collection of entry data and project implementation occurred during the second school term, three months into the school year.…”
Section: Resultsmentioning
confidence: 99%
“…It is recognised that knowledge is personalised, often differing to the knowledge held by others (Cobb, 1994;Nicholas & Paatsch, 2014). It can therefore be appreciated why early users of digital technologies in education, acknowledging this newfound avenue through which to individualise learning, made use of drill and practice for closed "pre-determined learning goals", offering users instant feedback as they engaged in "self-paced learning" (Jones, 2009, n.p).…”
Section: Drill and Practicementioning
confidence: 99%
“…The concept of readying early years children for academic success, basing educational practice on the content that children will encounter in assessments rather than on children's assessment results, was a practice that was evidenced in Nicholas and Paatsch [6]-the study that preceded this paper. The teachers of the five foundation-year classrooms that featured in Nicholas and Paatsch [6] used school-mandated standardized letter-identification assessments at the end of each child's first year of schooling. Results from the year that preceded the study showed that only 54 percent of foundation-year children were able to name each upper-and lower-case letter of the alphabet (52 letter symbols) and give a common sound for each (52 letter sounds) [6].…”
Section: The Study Contextmentioning
confidence: 99%
“…There is no question that assessments are useful tools for teachers when planning for teaching and learning [6]. However, in light of research that has found that some teachers teach to the test [4,5], with some early childhood educators targeting specific readingrelated outcomes in isolation [7], there is concern that pressure to ensure that children (and schools) will perform well in national literacy tests may devolve the teaching and learning of reading into a narrow objective to meet particular reading outcomes, 'readying' children from a younger and younger age to meet expected outcomes in their future schooling.…”
Section: Introductionmentioning
confidence: 99%
“…through audio‐visual songs and/or during shared reading experiences). Others require more targeted and extended support to develop this initial phase of awareness (Nicholas and Paatsch, 2014); an awareness that is based upon the fact that,
“ phonological segmentation and alphabetic coding skill are in a tightly intertwined reciprocal relationship in the early stages of reading acquisition and that these skills are mutually facilitative ” ( Stanovich and Stanovich, 1995, p. 95).
…”
Section: Introductionmentioning
confidence: 99%